Neutrophil Gelatinase-Associated Lipocalin (NGAL) measured at admission is associated with development of late cardiogenic shock and mortality in patients with STEMI. (26th April 2021) - Frydland, M; Moegelvang, R; Moeller, JE; Moeller-Helgestad, O; Holmvang, L; Mark, PD; Jensen, LO; Hassager, C
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Rigshospitalets Forskningsfond (Grant number: 07IO) Hjerteforeningen (Grant number A6024) Lundbeckfonden (Grant number R186-2015-2132) BACKGROUND: In patients with ST-elevation myocardial infarction (STEMI) increased inflammatory response is associated with development of cardiogenic shock (CS). Neutrophil Gelatinase-Associated Lipocalin (NGAL) is a glycoprotein released from mature neutrophils and the plasma concentration of NGAL likely increases immediately after STEMI. PURPOSE: We aimed to assess whether admission NGAL plasma concentration in patients with STEMI was associated with CS development after leaving the catheterization laboratory (late CS) and 30-day all-cause mortality. MATERIALS AND METHODS: From 1892 consecutive patients with STEMI 1626 (86%) had plasma NGAL concentration measured upon hospital admission before angiography throughout a 1-year period at two tertiary heart centers in Denmark. Patients were stratified according to NGAL quartiles (Q1-4). To assess late CS development, we adjusted for the Observatoire Régional Breton sur l'Infarctus (ORBI) risk score for late CS. For mortality assessment, we adjusted for gender, age, post-PCI culprit Thrombolysis in myocardial infarction (TIMI) flow, left ventricular ejection fraction (LVEF), kidney dysfunction, admission lactate concentration and being comatose after cardiac arrest. RESULTS: Increasing NGAL concentration was associated with higher age, more comorbidities (hypertension, diabetes, heart failure, previous stroke, and kidney dysfunction) and more critical patient conditions at presentation including lower blood pressure and LVEF. Plasma NGAL concentration was associated with both late CS development and 30-day mortality (Figure). When adjusted for factors associated with poor outcome, NGAL remained independently associated with both late CS development (Q4 vs. Q1-3) (OR (95% CI) 2.64 (1.57-6.03)) and 30-day mortality (HR (95% CI) 3.18 (1.46-6.93)). CONCLUSION: High admission plasma concentration of NGAL in patients with STEMI was independently associated late CS development and 30-day all-cause mortality.